ANALISIS REAKSI PASAR MODAL INDONESIA TERHADAP KEBIJAKAN TARIF IMPOR AMERIKA SERIKAT: STUDI PERISTIWA PADA PERUSAHAAN EKSPORTIR APRIL 2025 - Anugroho, Sigit; Fatah, Khoirul (JURNAL ILMIAH EDUNOMIKA, 2025)
This study analyzes the Indonesian capital market response to the implementation of United States import tariff policies, focusing on the stock price behavior of exporting companies. The research aims to identify the existence of significant abnormal returns and measure market reaction differences between pre and post-tariff announcement periods. Event study methodology was applied with an 11-day trading window (t-5 to t+5) examining five exporting issuers with minimum 10% exposure to the US market. Secondary data was obtained from Indonesia Stock Exchange during April 2025, analyzed using market-adjusted model to calculate abnormal returns and average abnormal returns. Hypothesis testing was conducted through one-sample t-test and Wilcoxon signed-rank test. Research findings demonstrate that the market exhibited no significant reaction on the event date, however significant abnormal returns were discovered at t+5 period with significance value of 0.021. Comparison of average abnormal returns between pre and post-event showed no statistically significant differences (p-value 0.500). The findings indicate delayed market reaction phenomenon and suboptimal efficiency of Indonesian market in responding to global economic information. This research contributes to event study literature in emerging markets by demonstrating delayed response characteristics toward international policy shocks.